Предмет: Алгебра,
автор: bakunina99
Решить уравнение
(2х - 1)(3х+7)-(1+6х)(х+2)=4
Ответы
Автор ответа:
0
(2х - 1)(3х+7)-(1+6х)(х+2)=4
6х^2+14х-3х-7-(х+2+6х^2+12х)=4
6х^2+11х-7-х-2-6х^2-12х=4
-9-2х=4
-2х=4+9
-2х=13
х=13:(-2)
х=-6,5
Ответ:х=-6,5.
Автор ответа:
0
__________________________________________________________________
Похожие вопросы
Предмет: Биология,
автор: Аноним
Предмет: Математика,
автор: Rongster
Предмет: Алгебра,
автор: adelyabaibulatova
Предмет: Алгебра,
автор: ГелиоГрафиня
Предмет: Геометрия,
автор: Lyuda2079220